2021
DOI: 10.1002/asia.202101256
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective synthesis of primary amines from amide over Ru‐Nb2O5 catalysts

Abstract: Amines are an important class of compounds in natural products and medicines. The universal availability of amides provides a potential way for the synthesis of amines. Herein, Ru/Nb 2 O 5 catalyst is demonstrated to be highly efficient and stable for the selective hydrogenation of propionamide to propylamine (as a model reaction), with up to 91.4% yield of propylamine under relatively mild conditions. Results from XPS analyses, CO chemisorption, TEM images and DRIFTS spectra revealed that the unique propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…† Hereafter, Guo et al reported an efficient Ru/Nb 2 O 5 catalyst for the hydrogenation of propionamide to propylamine, achieving up to 91.4% yield. 85 Also, in this case, the addition of NH 3 was found to be essential for achieving high selectivity in the hydrogenation of aliphatic acyclic amides. This is attributed to the low steric hindrance of the desired amines that tend to dimerize, while the presence of NH 3 traps the intermediate, forming primary amines.…”
Section: Hydrogenation Of Aliphatic Acyclic Amidesmentioning
confidence: 93%
See 1 more Smart Citation
“…† Hereafter, Guo et al reported an efficient Ru/Nb 2 O 5 catalyst for the hydrogenation of propionamide to propylamine, achieving up to 91.4% yield. 85 Also, in this case, the addition of NH 3 was found to be essential for achieving high selectivity in the hydrogenation of aliphatic acyclic amides. This is attributed to the low steric hindrance of the desired amines that tend to dimerize, while the presence of NH 3 traps the intermediate, forming primary amines.…”
Section: Hydrogenation Of Aliphatic Acyclic Amidesmentioning
confidence: 93%
“…Firstly, the Ru/Nb 2 O 5 catalyst was demonstrated to be highly efficient and stable for the selective hydrogenation of propionamide to propylamine, which could be a promising approach for selective propylamine synthesis. 85 Characterization techniques revealed that Nb 2 O 5 can effectively activate the amide CvO group. Moreover, small-sized Ru particles are very efficient hydrogenation sites.…”
Section: Critical Review Green Chemistrymentioning
confidence: 99%